2017
DOI: 10.5507/fot.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

Komarekiella atlantica gen. et sp. nov. (Nostocaceae, Cyanobacteria): a new subaerial taxon from the Atlantic Rainforest and Kauai, Hawaii

Abstract: Six strains of Cyanobacteria sampled in the Brazilian Atlantic rainforest and one strain from Kauai, Hawaii, were studied using morphological and molecular approaches, including 16S rRNA gene phylogenies and 16S-23S ITS secondary structures, and are herein described as Komarekilla atlantica gen. et sp. nov.. Morphologically they are similar to Nostoc, Desmonostoc, Halotia, and Mojavia and indistinguishable from Chlorogloeopsis. The parsimony and Bayesian phylogenies of the 16S rDNA show that these strains are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 28 publications
2
60
0
1
Order By: Relevance
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities ( Sphaerospermopsis and Nodularia), rock-dwelling communities ( Scytonema and Tolypothrix ), and hot spring cyanobacteria mats ( Desertifilum and Gloeotrichia ) (Dadheech et al, 2014; Mazur-Marzec et al, 2015; Gkelis et al, 2017; Joanna and Andrzej, 2018). Our results revealed the presence of taxa not previously described from Greek habitats (Gkelis et al, 2016), such as Allinostoc (Saraf et al, 2018) and Oculatella (Osorio-Santos et al, 2014) and taxa previously described only from the tropical zone like Komarekiella and Kovacikia (Miscoe et al, 2016; Hentschke et al, 2017). Furthermore, the Geitleria calcarea strain isolated in this study, to the best of our knowledge, is the first isolate in world’s cyanobacteria culture collections depositories (Friedmann, 1979; Coute, 1989), whilst Chlorogloea sp.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The polyphasic taxonomy applied to the strains of this study revealed taxa known to be part of bloom-forming communities ( Sphaerospermopsis and Nodularia), rock-dwelling communities ( Scytonema and Tolypothrix ), and hot spring cyanobacteria mats ( Desertifilum and Gloeotrichia ) (Dadheech et al, 2014; Mazur-Marzec et al, 2015; Gkelis et al, 2017; Joanna and Andrzej, 2018). Our results revealed the presence of taxa not previously described from Greek habitats (Gkelis et al, 2016), such as Allinostoc (Saraf et al, 2018) and Oculatella (Osorio-Santos et al, 2014) and taxa previously described only from the tropical zone like Komarekiella and Kovacikia (Miscoe et al, 2016; Hentschke et al, 2017). Furthermore, the Geitleria calcarea strain isolated in this study, to the best of our knowledge, is the first isolate in world’s cyanobacteria culture collections depositories (Friedmann, 1979; Coute, 1989), whilst Chlorogloea sp.…”
Section: Discussionsupporting
confidence: 56%
“…strains we isolated here are reported for the first time as cave inhabitants. Hentschke et al (Hentschke et al, 2017),based on intensive examination of species life cycle, proposed the new genus Komarekiella and classified the strains from both Hawaiian and Brazilian rainforests in the single Komarekiella atlantica species. Our phylogenetic analysis of 16-23S and cpcBA -IGS sequences, as well as the different climatic zone and habitat, suggests that strains TAU-MAC 0117 and 0217, may belong to a new taxon, thus further research is required to describe it.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming difficult to clearly differentiate closely related taxa based solely on morphology owing to the huge amount of heterogeneity (Singh et al 2016). Furthermore, molecular data indicate that the genetic diversity within this genus exceeds its morphological diversity, clearly supporting its polyphyletic status (Rajaniemi et al 2005a, 2005b, Řeháková et al 2007, Hrouzek et al 2013, Genuário et al 2015, Bagchi et al 2017, Hentschke et al 2017. Therefore, the genus Nostoc requires continuously taxonomic re-evaluation and the establishment of diacritical features.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional definition of Nostoc includes several distinct but not closely related phylogenetic clusters, some of which have been already formally separated from Nostoc, such as Mojavia (Řeháková et al 2007) and Desmonostoc (Hrouzek et al 2013). In recent years, many studies using the polyphasic approach led to the establishment of more novel genera by splitting from Nostoc (Genuário et al 2015, Bagchi et al 2017, Hentschke et al 2017, Cai et al 2019a, 2019b. In China, the investigation on cyanobacteria from all kinds of environmental conditions and researches on cyanobacterial taxonomy ments aggregated and entangled irregularly in gelatinous colonies, and usually shown as macroscopic with peripheral periderm enveloping the whole spherical colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation